1998
DOI: 10.1097/00001756-199801260-00026
|View full text |Cite
|
Sign up to set email alerts
|

Tolerization against loss of neuronal function after ischemia–reperfusion injury

Abstract: To investigate whether sublethal ischemia preserves neuronal function otherwise lost after stroke, anesthesized rabbits were subjected to clamping of abdominal aorta to cause lumbar spinal cord ischemia. An occlusion period of 12.5 min was followed 12 or 48 h later by a second occlusion for 30 min. When scored 24 h later for hindlimb function on a 0-6 scale, the rabbits that underwent tolerizing ischemia 12 h before infarction had better motor function (n = 7; 4.29+/-0.21,p < 0.0001) than sham-operated control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 8 publications
1
19
1
Order By: Relevance
“…Cheng et al showed that the later waves of SSEP are more sensitive to ischemia and disappear concomitantly with the decrease of N1 wave amplitude more than 6 min after the induction of spinal cord ischemia in rabbits [18]. Using similar animal species, de Haan et al [19] and Ueno et al [11] did not demonstrate induction of spinal cord ischemic tolerance with short periods of sudlethal stress, while Matsumoto et al [4], Munyao et al [6] and Sakurai et al [7] successfully used longer periods of ischemic preconditioning. On the other hand, the response of SSEP to spinal cord ischemic induction seems to be more precocious in dogs [17], justifying the use of short periods of aortic crossclamping in the preconditioning cycles in the present experimental protocol.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Cheng et al showed that the later waves of SSEP are more sensitive to ischemia and disappear concomitantly with the decrease of N1 wave amplitude more than 6 min after the induction of spinal cord ischemia in rabbits [18]. Using similar animal species, de Haan et al [19] and Ueno et al [11] did not demonstrate induction of spinal cord ischemic tolerance with short periods of sudlethal stress, while Matsumoto et al [4], Munyao et al [6] and Sakurai et al [7] successfully used longer periods of ischemic preconditioning. On the other hand, the response of SSEP to spinal cord ischemic induction seems to be more precocious in dogs [17], justifying the use of short periods of aortic crossclamping in the preconditioning cycles in the present experimental protocol.…”
Section: Discussionmentioning
confidence: 96%
“…This process involves endogenous cellular protective mechanisms, that include an early and a late phase of protection [15]. Although several authors have previously demonstrated the delayed protection seen with brief periods of ischemic induction on the spinal cord [4][5][6][7], the acute effects of immediate ischemic preconditioning on that organ have been controversial. Some studies have shown significant impact of previous periods of ischemic induction some minutes before prolonged aortic occlusion in the prevention of spinal cord injury [9,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process involves cell protection mechanisms that include a phase of early protection as well as a late one 18 . Although some authors have previously demonstrated the late protection phase of IP [19][20][21][22]27 , the acute effects of immediate IP have been controversial. Some studies have shown a significant impact of previous periods of ischemic induction some minutes before the prolonged occlusion of the aorta, in the prevention of spinal cord injury 24,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an apparent efficacy of IP in protecting against spinal cord ischemia, with the benefit being obtained mainly when the procedure is performed 1 or 2 days before a prolonged ischemic injury [19][20][21] . On the other hand, the acute IP of the spinal cord, potentially more likely to be incorporated to clinical practice, has shown controversial results [22][23][24][25][26] , especially due to a failure in the adequate control of ischemia and reperfusion time, necessary to achieve its effect.…”
Section: Introductionmentioning
confidence: 99%